2012
DOI: 10.1186/1743-422x-9-210
|View full text |Cite
|
Sign up to set email alerts
|

Stability studies of HIV-1 Pr55gagvirus-like particles made in insect cells after storage in various formulation media

Abstract: BackgroundHIV-1 Pr55gag virus-like particles (VLPs) expressed by baculovirus in insect cells are considered to be a very promising HIV-1 vaccine candidate, as they have been shown to elicit broad cellular immune responses when tested in animals, particularly when used as a boost to DNA or BCG vaccines. However, it is important for the VLPs to retain their structure for them to be fully functional and effective. The medium in which the VLPs are formulated and the temperature at which they are stored are two imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 22 publications
(34 reference statements)
0
25
0
Order By: Relevance
“…It has been shown that the HIV-1Pr55 gag virus like particles (VLP) could be stabilized and protect from storage induced damage by three different osmolytes namely, trehalose, sucrose and sorbitol. 90 It was found that sucrose stabilizes VLP for six months at both −20°C and −70°C. Trehalose on other hand showed protection in stability for a longer time period, wherein after 12 months at −20°C, only 10% to 40% of the VLP showed altered morphology while at −70°C, there were no changes in the morphology of VLP.…”
Section: Long Term Storagementioning
confidence: 98%
“…It has been shown that the HIV-1Pr55 gag virus like particles (VLP) could be stabilized and protect from storage induced damage by three different osmolytes namely, trehalose, sucrose and sorbitol. 90 It was found that sucrose stabilizes VLP for six months at both −20°C and −70°C. Trehalose on other hand showed protection in stability for a longer time period, wherein after 12 months at −20°C, only 10% to 40% of the VLP showed altered morphology while at −70°C, there were no changes in the morphology of VLP.…”
Section: Long Term Storagementioning
confidence: 98%
“…Even under stable cold chain conditions, the longevity of VLP can be limited. This can be prolonged by storage at temperatures at or below −20°C, stabilized with the addition of a cryopreservative such as glycerol or trehalose [146]; however, this only further exacerbates the issue of delivering these vaccines intact where they are needed, such as in developing countries without reliable cold-chain delivery infrastructure. Alternative storage methods such as freeze-drying, or lyophilization, can have variable effects on the stability of VLP.…”
Section: Excipientsmentioning
confidence: 99%
“…Often samples prepared for immunoelectron microscopy are ultrathin sections of tissue treated for microscopy applications, but valuable information can also be obtained from immunogold labeling of liquid samples of viral suspensions. Not only can these techniques be applied to studying live viruses, but they are also useful for characterizing viral components in vaccines, viral‐like particles, proteins purified from viruses, and other specimen relevant in modern virology applications (Gallagher et al., ; Lynch, Meyers, Williamson, & Rybicki, ). Immunoelectron microscopy has also been applied to study many other molecular biology and nanotechnology specimens (Bruckman, Randolph, Gulati, Stewart, & Steinmetz, ; Geuze et al., ; Zuber, Spiro, Guhl, Spiro, & Roth, ).…”
Section: Introductionmentioning
confidence: 99%